PERAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH MEMODERASI PENGARUH MOTIVASI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU (Studi Kasus Pada SMA Negeri Di Kecamatan Pati Kabupaten Pati) - Kastini, 12.5202.0186; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the influence of motivation and organizational commitment to the teacherâs performence of Public Senior High School with moderation of transformasional leadership. The specific study of this study is to examine the role of transformasional leadership moderates the influence of motivation and organizational commitment e to the teacherâs performance. The usefulness of this study is toÂ explain andÂ extebnd previous study on the role of transformasional leadership moderate the influence of motivation and organizational commitment to the teacherâs performance. This study used a population of high school teachers in Pati district, Pati regency were 116 teachers. Sampling techniques in this study is non-probability sampling with purposive sampling method. The analysis technique used is the regression model of quasi moderation The resultÂ the writer can follows: The motivation influents the teacherâs performance positively, the organizational commitment influents the teacherâs performanec positively, the transformational leadership also influents the teacherâs performance positively, the transformational leadership strengthen the influence ofÂ motivation to the teacherâs performance, the transformational leadership does not moderate the influenceÂ of organizational commitment to the teacherâs performance Keywords: motivation,Â organizational commitment, transformational leadership and teacherâs performance